Diagnostic Utility Of Trichoscopy In Tinea Capitis A Systematic Review of Studies Using Mycological Confirmation - Enik Srihartati (Universitas Muhammadiyah Surabaya, 2026)
Background: Tinea capitis can mimic alopecia areata, seborrhoeic dermatitis, psoriasis and bacterial folliculitis. Mycological confirmation remains important, but potassium hydroxide microscopy is operator dependent and fungal culture may delay diagnosis. Trichoscopy enables rapid visualisation of characteristic hair-shaft and scalp abnormalities. Objective: To evaluate the diagnostic utility of trichoscopy in tinea capitis, including diagnostic accuracy, common signs and associations with dermatophyte species. Methods: Original human studies published from January 2016 to 27 July 2026 were identified through PubMed/MEDLINE, PubMed Central, publisher platforms and citation lists. Eligible studies assessed trichoscopy or scalp dermoscopy and incorporated potassium hydroxide microscopy, fungal culture and/or polymerase chain reaction. Findings were narratively synthesised because of heterogeneity. Results: Eight studies involving 640 participants were included. One prospective multicentre study reported 94% sensitivity, 83% specificity, 92% positive predictive value and 86% negative predictive value for at least one typical trichoscopic feature. Comma hairs, black dots, broken hairs and scaling were common. Reported species-associated patterns varied across geographic settings. Conclusion: Trichoscopy is a rapid adjunct for recognising tinea capitis and prioritising mycological testing. It should not replace potassium hydroxide microscopy or fungal culture, while species prediction remains insufficiently reliable for treatment decisions.